Anesthetic Management of a Parturient with Poliomyelitis Associated with Kyphoscoliosis - Shrestha, AB; Shrestha, S; Sharma, KR; Gurung, T (Nepal Journal of Obstetrics and Gynaecology, 2014)
A 27-year-old primigravida with poliomyelitis associated with kyphoscoliosis underwent cesarean section under spinal anesthesia. Anesthesia poses a significant risk to a parturient with kyphoscoliosis and there is no single regimen that can be recommended for anesthetic management. Regional anesthesia is also challenging for anesthesiologist because the distortion of the spinous process and rotation of the vertebral column. The perioperative period was uneventful. Spinal anesthesia can be safely administered with less adverse effects in poliomyelitis patients with kyphoscoliosis. DOI: http://dx.doi.org/10.3126/njog.v9i1.11193 NJOG 2014 Jan-Jun; 2(1):67-70